Pattern analysis of yield for oats cultivars in Iran - Mohamadinejad, Ghasem; Rezai, Abdolmajib (MTT, 2004)
Several statistical methods have been developed to describe the responses of genotypes to variation in the environment. Amongst them, Additive Main effects and Multiplicative Interactions (AMMI) analysis (Zobel 1988) is particularly effective for depicting adaptive responses. Because yield trails frequently have both significant main effects and a significant genotype × environment interaction and traditional statistical analysis are not always effective with this data structures. AMMI analysis was used to evaluate yield stability of nine oats genotypes (4 Canadian cultivars and 5 Turkish breeding lines) and Makoi barley (as check) in 6 environments (3 dates of planting and 3 sowing densities of 300, 375 and 450 seeds / m2). The experiment was conducted at Research farm of Isfahan University of Technology in 2001. For each environment a randomized complete design with 3 replications was used. The main effects of genotypes, environment and genotype × environment interaction effects were significant (p<0.01) and 70% of interaction sum of squares was explained by the first two principal components. Biplot of genotypic and environmental components of the first interaction principal component (IPC1) and mean yields of the genotypes and environments relieved that Boyer and Line 28 were the most stable genotypes and Boyer had the lowest IPC1.Pacer and Lines No. 2 and 17 were the least stable genotypes. Biplot of IPC2 and means of yield also showed that Boyer was the most stable genotypes. Discrimination of genotypes based on stability statistics of AMMI model (EV2 & SIPC2) showed that Boyer and Calibre were the most stable genotypes. Pattern analysis of the two significant principal components confirmed that Boyer was the most stable genotypes and is suitable cultivar for breeding program or introduction for commercial production. Based on this pattern analysis Lines No.17 and 2 had specific adaptation to first sowing density (300 seed /m2). Lines No. 32 and 28 showed specific adaptation to fi×rst planting date (12 Oct.) Makoi and Pacer had the specific adaptation to second and third planting date and second sowing density. Annicchiarico, P., 1997, Theoretical and Applied Genetics, No. 94, PP. 1072 1077; Chapman, S.C. et al. 1997, Euphytica, 95:1 9; Zobel, R.W. et al. 1988, Agronomy Journal 80:388 393.
Keywords: Ka; G×E Interaction; pattern analysis; AMMI; biplot